Pengaruh Kompensasi, Kompetensi, Dan Motivasi Pada Produktivitas Kerja Pegawai Pt. Jasa Marga (Persero) Tbk. Cabang Palikanci - Ni Wayan Fitriana Ayu Lestari; Isti Riana Dewi; Aan Kanivia (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2021)
There is job dissatisfaction that some employees at PT. Jasa Marga (Persero) Tbk. The Palikanci branch resulted in low work productivity. This study took a sample of 58 employee respondents. The technique of taking using purposive sampling was collected through a questionnaire instrument aimed to determine the effect of compensation, competence, and motivation on work productivity. The analysis technique uses multiple regression analysis. It was found that there was a positive and significant influence between the variables of compensation, competence, motivation on work productivity at PT. Jasa Marga (Persero) Tbk. Palikanci branch either partially or simultaneously. So it is necessary to pay attention to the company so that it can pay more attention to the amount of compensation given and appreciation of employee competence to increase work productivity. Likewise, high motivation must be evaluated to increase work productivity which will help the company achieve its goals.